Simulation and sensitivity analysis of autothermal reforming (ATR) for mobile fuel cell application - Ahmad, Arshad; Ibrahim, Norazana (Universiti Malaysia Sabah, 2003)

(untitled)
Autothermal Reforming (ATR) is one of the latest technologies for fuel reforming to produce hydrogen for fuel cell automotive application. ATR is a combination of an endothermic and exothermic process to give the maximum hydrogen productivity. It integrates the heat effect of partial oxidation and steam reforming reactions by feeding the fuel, water and air or oxygen into the reactor. This process is carried out in the presence of a catalyst, which controls the reaction pathways and thereby reforming reaction. In this paper, the development of ATR simulation model using MATLAB/SIMULINK environment is presented. Based on this model, the sensitivity analysis of the process is performed. The results of this study are discussed.